Bluetooth Enabled Data Collector for Wireless Sensor Networks - Garcia, Cristiane Silva; Eckard, Diego; Netto, João Cesar; Pereira, Carlos Eduardo; Müller, Ivan (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2015: Anais do V Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2015)
The wireless sensor networks (WSN) are gradually gaining attention because it is a key technology for the Internet of Things. For most of these networks, the data is usually collected in a manual way, by removing a memory unit or connecting the collector node to a personal computer. This is a constraint, because it demands the manipulation of the collector radio by the operator, which consists in a problem in practical applications. The main goal of this work is to present a non-invasive alternative way to collect the data by means of Bluetooth technology. The approach allows the development of hermetic devices, which is a desirable feature for practical deployment of the sensor nodes.